Indonesia Stock Price Index, Inflation, Interest Rate and Exchange Rate against ISSI - Khoirun Nisa’atus Sholihah; Niken Savitri Primasari (Universitas YARSI, 2021)
The purpose of this study is to examine the effect of Indonesia regional stock price index, inflation, interest rate, and exchange rate on ISSI, for Singapore, Malaysian and Philippine. The dependent variable in this study is ISSI. The independent variables in this study are Straits Times Index (STI), Kuala Lumpur Stock Exchange Index (KLSE), Philippine Stock Exchange Index (PSEI), Singapore inflation (INFSG), Malaysian inflation (INFMY), Philippine inflation (INFPH), Singapore interest rate (SBSG), Malaysia interest rate (SBMY), Philippine interest rate (SBPH), Singapore exchange rate (SGD), Malaysian exchange rate (MYR), and Philippine exchange rate (PHP). The sample of this study are all variables starting in 2014-2019. Analysis tools to test hypotheses using the VECM method. The analysis shows that the variables that have positive and significant effect on ISSI are KLSE, INFSG, SBSG, SGD, MYR, and PHP. SBMY has a positive but not significant effect on ISSI. While the variables that have negative and significant influence are PSEI, INFPH, and SBPH.